2022
DOI: 10.1038/s41467-022-34616-8
|View full text |Cite
|
Sign up to set email alerts
|

A population-based serological study of post-COVID syndrome prevalence and risk factors in children and adolescents

Abstract: Post-COVID syndrome remains poorly studied in children and adolescents. Here, we aimed to investigate the prevalence and risk factors of pediatric post-COVID in a population-based sample, stratifying by serological status. Children from the SEROCoV-KIDS cohort study (State of Geneva, Switzerland), aged 6 months to 17 years, were tested for anti-SARS-CoV-2 N antibodies (December 2021-February 2022) and parents filled in a questionnaire on persistent symptoms in their children (lasting over 12 weeks) compatible … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A third meta -analysis was published by Notarte et al, 17 and it included 37 peer -reviewed studies and 1 preprint screened through September 15, 2022. Most of the reviewed articles found that the symptoms of long -COVID -19 were associated with older age (though not reaching statistical significance in the meta -analysis; P = 0.17), A population -based study exploring the prevalence and risk factors of post -COVID syndrome in children and adolescents has also been recently published by Dumont et al 27 The authors followed -up for at least 12 weeks a total number of 1034 Swiss patients aged 6 months to 17 years, 570 (55.1%) of whom displayed anti-SARS -CoV -2 antibodies. In seropositive children, the rate of persistent symptoms was 9.1% (95% CI, 6.7%-11.8%).…”
mentioning
confidence: 99%
“…A third meta -analysis was published by Notarte et al, 17 and it included 37 peer -reviewed studies and 1 preprint screened through September 15, 2022. Most of the reviewed articles found that the symptoms of long -COVID -19 were associated with older age (though not reaching statistical significance in the meta -analysis; P = 0.17), A population -based study exploring the prevalence and risk factors of post -COVID syndrome in children and adolescents has also been recently published by Dumont et al 27 The authors followed -up for at least 12 weeks a total number of 1034 Swiss patients aged 6 months to 17 years, 570 (55.1%) of whom displayed anti-SARS -CoV -2 antibodies. In seropositive children, the rate of persistent symptoms was 9.1% (95% CI, 6.7%-11.8%).…”
mentioning
confidence: 99%
“…The prevalence of long COVID obtained is very similar to the 4.1% reported in a recent Swiss study comparing the prevalence of persistent symptoms in 570 infected children under 18 years of age with a control group. 6 These findings contrast with the prevalence of 14.6% in a pediatric multicenter study in Madrid, Spain. 4 It is possible that the difference is because their patients were more severely affected.…”
Section: Discussionmentioning
confidence: 65%
“…Other risk factors described in the literature have been age >12 years, having comorbidities (mainly obesity and allergy) or having been hospitalized. 2,5,6,8 The most frequent persistent symptoms were anosmia, fatigue and difficulty concentrating. The prevalence of anosmia obtained is much higher than the 1.7% reported in an Italian study, which highlights the impact that this symptom can have on children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations